Pengaruh Pendidikan Kesehatan Metode Video Terhadap Tingkat Pengetahuan Tentang Diare Pada Anak di SD Negeri 1 Sokaraja Tengah - Annisha Febiyani; Ikit Netra Wirakhmi; Surtiningsih Surtiningsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Diarrhea remains a health problem in developing countries such as Indonesia and is a major cause of mortality and mobility, especially in children. The prevalence of diarrhea based on symptoms is calculated by combining diagnosed or symptomatic diarrhea cases. The incidence and prevalence of diarrhea in Indonesia are 3.5% and 7.0%. This study aims to determine whether there is an effect of health education on the level of knowledge about diarrhea in children at SD Negeri 1 Sokaraja Tengah. This research method uses quasi experimental with One group pretest-posttest design. The sampling technique used total sampling with a sample size of 56 students. Data was taken using a questionnaire. The results showed that the majority of female gender with 29 respondents (51.8%). There is a difference in the level of knowledge about diarrhea before and after being given health education. Based on statistical tests using the paired t test results in a p value of 0.000 which means there is a significant effect.